Full regeneration of descending corticotropin-releasing hormone axons after a complete spinal cord injury in lampreys - Laura González-Llera; Daniel Sobrido-Cameán; Gabriel N. Santos-Durán; Antón Barreiro-Iglesias (Computational and Structural Biotechnology Journal, 2022)
Sea lampreys are a vertebrate model of interest for the study of spontaneous axon regeneration after spinal cord injury (SCI). Axon regeneration research in lampreys has focused on the study of giant descending neurons, but less so on neurochemically-distinct descending neuronal populations with small caliber axons. Corticotropin-releasing hormone (CRH) is a neuropeptide that regulates the stress response or locomotion. CRH is also a neuropeptide of interest in the SCI context because descending CRHergic projections from the Barrington’s nucleus control micturition behavior in mammals. Recent work from our group revealed that in sea lampreys the CRHergic innervation of the spinal cord is only of descending origin. Thus, the lack of intrinsic CRH spinal cord neurons provides the opportunity to analyze the regeneration of this descending system by using immunofluorescence methods. Here, we used an antibody against the sea lamprey mature CRH peptide, confocal microscopy, lightning adaptive deconvolution, and ImageJ to analyze the regenerative capacity of the descending CRH-immunoreactive (-ir) axons of larval sea lampreys after a complete SCI at the level of the fifth gill. At 10 weeks post-lesion, when behavioral analyses showed that injured animals had recovered normal appearing locomotion, our results revealed a full recovery of the number of CRH-ir profiles (axons) at the level of the sixth gill. Thus, the CRH descending axons of lampreys fully regenerate after a complete SCI. Our study provides a new model to study spontaneous and successful axonal regeneration in a specific neuronal type with small caliber axons by using simple immunohistochemical methods.